Factors Affecting Start-Up Failure in Kathmandu Valley - Pokhrel, Anshu Sharma (Nepalese Journal of Economics, 2025)
This study examines the factors affecting start-up failure in Kathmandu Valley. Start-up failure is the dependent variable. The selected independent variables are political issues, lack of capital, fear of failure, poor team and lack of entrepreneurial knowledge/skills. The primary source of data is used to assess the opinion of respondents regarding political issues, lack of capital, fear of failure, poor team, lack of entrepreneurial knowledge/ skills and start-up failure. The study is based on primary data of 140 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the factors affecting start-up failure in Kathmandu Valley. The study showed a positive impact of lack of capital on start-up failure. It indicates that lack of capital leads to start-up failure. Similarly, the study showed a positive impact of political issues on start-up failure. It indicates that higher the political influence higher the chance of being start-up failure. Likewise, the study showed a positive impact of fear of failure on startup failure. It indicates that owners who have fear of failure are likely to have failed their startups. Further, the study showed a positive impact of lack of entrepreneurial knowledge and skills on start-up failure. It indicates that owners who have no entrepreneurial knowledge and skills that leads to fail start-ups. In addition, the study showed a positive impact of poor team on start-up failure. It indicates that existence of poor team leads to start-up failure.